A comparison of mother and father reports of children's theory of mind: further validation of the children's social understanding scale. Issue 3 (4th May 2021) - Gluck, Stephanie C.; Tahiroglu, Deniz; Moses, Louis J.
ABSTRACT: The reliability and validity of the Children's Social Understanding Scale (CSUS) was further assessed by examining fathers' as well as mothers' reports of children's social understanding, along with behavioural measures of children's mental state understanding. 112 families with children aged 38 to 64 months participated with both parents filling out the CSUS, while children were administered a language test and a battery of Theory of Mind (ToM) tasks. Internal consistency of the CSUS was high for both mothers and fathers, and maternal and paternal CSUS scores were moderately-highly correlated. In addition, mothers' and fathers' CSUS responses were each associated with children's behavioural ToM, even after controlling for age and verbal ability. Finally, both parents appeared to have roughly equally strong insights into their children's ToM and each parent's insight did not appear to add novel information about ToM over and above that of the other parent. These findings suggest that the CSUS is a reliable and valid tool in assessment of ToM by both mothers and fathers, and that researchers can safely use either one or the other as a complement to behavioural performance in studying ToM.